Sammansättningar i ordboksarbetet, med utgångspunkt från TEATER - Stille, Per (Nordiske Studier i Leksikografi, 2003)
The Scandinavian languages have nearly unlimited possibilities to form compounds. When working with dictionaries you often deal with problems regarding which compounds ought to be included and which to be excluded. These problems of course depend on the kind of dictionary you are working on. In addition to the general principles you have to formulate easily followed guide-lines directed to the practical daily work. In this article some thoughts concerning these problems are dealt with emanating from my work with the word TEATER in the editorial work with the Swedish Academy Dictionary.